Teachers’ and Students' Perspective on Implementation of Merdeka Curriculum - Ocktin Mahashelly Elok Setya; Putu Dian Danayanti Degeng (International Journal Labs, 2025)
This study examines teachers’ and students’ perspectives on the implementation of the Merdeka Curriculum in English language learning at SMPN 6 Kota Kediri, Indonesia. Adopting a qualitative descriptive design, data were collected through semi-structured interviews with two English teachers and six purposively selected students from different classes. Thematic analysis indicated that the curriculum promotes flexibility, creativity, and student-centered learning through projects, group discussions, and the use of interactive media. Teachers valued the autonomy to adapt instructional content to students’ interests and needs, while students appreciated the variety and engagement of learning activities. Nevertheless, several challenges were identified, including limited vocabulary, difficulty understanding instructions in English, low classroom participation due to shyness, inadequate learning facilities, and disparities in student ability levels. A notable perception gap emerged, with teachers believing that creativity and autonomy were sufficiently embedded, whereas some students perceived their learning needs as unmet. The findings underscore that successful implementation of the Merdeka Curriculum requires clear instructional guidelines, equitable resource allocation, differentiated teaching strategies, integration of interest-based learning, and ongoing professional development for teachers. This study contributes to the discourse on curriculum reform in junior secondary education and highlights the necessity of aligning policy intentions with classroom realities.